2022
DOI: 10.3390/ijms23126362
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation Increases Axonal Growth from Dorsal Root Ganglia Co-Cultured with Schwann Cells in Highly Aligned PLA-PPy-Au Microfiber Substrates

Abstract: Nerve regeneration is a slow process that needs to be guided for distances greater than 5 mm. For this reason, different strategies are being studied to guide axonal growth and accelerate the axonal growth rate. In this study, we employ an electroconductive fibrillar substrate that is able to topographically guide axonal growth while accelerating the axonal growth rate when subjected to an exogenous electric field. Dorsal root ganglia were seeded in co-culture with Schwann cells on a substrate of polylactic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 102 publications
0
7
1
Order By: Relevance
“…Interestingly, the in vitro delivery of DHX or BDNF within electrospun PLA fibers follows a similar profile as the PLA-curcumin membrane fibers, with a linear, rapid delivery profile for the first week followed by a slower rate of delivery of the remaining cargo (Liu et al, 2022). We previously demonstrated that PLA nanofibers improved neurite growth and axonal guidance (Gisbert Roca et al, 2020;Gisbert Roca et al, 2021;Gisbert Roca et al, 2022), but as shown here, the addition of curcumin did not display any additive effect. Nevertheless, equivalent concentrations of sustained delivered curcumin from the PLA nanofibers could contribute to neuronal elongation and axonal growth in endogenous tissue; however, this phenomenon will need to be further evaluated in a longer-term study.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Interestingly, the in vitro delivery of DHX or BDNF within electrospun PLA fibers follows a similar profile as the PLA-curcumin membrane fibers, with a linear, rapid delivery profile for the first week followed by a slower rate of delivery of the remaining cargo (Liu et al, 2022). We previously demonstrated that PLA nanofibers improved neurite growth and axonal guidance (Gisbert Roca et al, 2020;Gisbert Roca et al, 2021;Gisbert Roca et al, 2022), but as shown here, the addition of curcumin did not display any additive effect. Nevertheless, equivalent concentrations of sustained delivered curcumin from the PLA nanofibers could contribute to neuronal elongation and axonal growth in endogenous tissue; however, this phenomenon will need to be further evaluated in a longer-term study.…”
Section: Discussioncontrasting
confidence: 47%
“…PLA substrates are suitable for NPC transplantation allowing adhesion, planar distribution, proliferation, migration, and differentiation (Li et al, 2021;Li et al, 2022) providing a less invasive transplantation and cell delivery method instead of direct injection into the SCI (Zholudeva and Lane, 2019). We recently demonstrated that these materials improved neurite outgrowth and axonal guidance (Gisbert Roca et al, 2020;Gisbert Roca et al, 2021;Gisbert Roca et al, 2022), making them an ideal candidate for NPC delivery and the repair of neuronal tissue damage. Additionally, our research has shown that delivering NPC in combination with curcumin directly to the injured spinal cord can promote neuroprotection and stimulate axonal growth (Requejo-Aguilar et al, 2017;Bonilla et al, 2021;Elkhenany et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A clinical study showed that the success rate of nerve conduit alone was more varied and less reliable in such cases [38]. The scaffold-free method could allow researchers to fabricate more complex structures to mimic actual nerves, such as using electrical stimulation to dictate the direction of motor neurons co-cultured with Schwann cells [39]. Our results indicate that early induction of SCAPs towards neural lineage using a small-molecule cocktail is beneficial in promoting sciatic nerve recovery but likely not sufficient for full recovery in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…However, the migration mechanism of Schwann cells is still unclear, which may be related to calcium gradients by ES, [114] ES-increased neurotrophin secretion, [115] the activation in mitogen-activated protein kinase (MAPK), [116] and so on. Due to the slow growth rate (1 mm per day) of nerve regeneration and the short growth duration (less than 1 year), [117] the existing migration efficiency of Schwann cells is still challenging to span the critical distance (e.g., 3 cm) of peripheral nerve regeneration. The adequate stimulus time, electric field, Schwann cell viability, and regenerative process are Electrical conductivity [42] [S cm 2-100 [42] High-performance capacitor, [43] rescue thrombolysis, [44] conductive scaffold, [45] flexible wearable devices, [46] drug nanocarrier-release system, [47] photothermal-converters, [48] biosensor, [49] osteogenic scaffold, [50] ion adsorption device.…”
Section: Polypyrrolementioning
confidence: 99%